A study of friending willingness on SNSs: Secondary school teachers' perspectives. (May 2017) - Kuo, Fu Wen; Cheng, Wen; Yang, Shu Ching
Abstract: This study examines the self-reported decision making behaviors of 435 Taiwanese in-service secondary school teachers' regarding their willingness to accept friend requests on social network sites (SNSs) from different requesters (e.g., students with acquaintanceships of various durations, unknown/in-class/homeroom students and teaching colleagues with or without administrative roles). The study found that teachers made different friending decisions based on gender and on the identity of the requester but found no difference in teachers' basic roles. That is, male teachers reported greater willingness to friend unknown students, in-class students and administrative colleagues than did female teachers. Overall, non-administrative colleagues were the most acceptable, whereas unknown students were the most unfavorable requesters. The study also revealed that teachers' friending willingness varies with the joint effects of privacy concerns and relational (social intimacy, ethical concerns) and behavioral (Facebook use and protective behaviors) factors. A privacy paradox exists in teachers' willingness to friend homeroom students and non-administrative colleagues. Teachers have privacy concerns related to all five types of requesters, but they report fewer privacy concerns and more ethical concerns and social intimacy when friending in-class and homeroom students. However, these teachers employ privacy protection practices only when friending unknown and in-class students and administrative colleagues. When friending colleagues, intensive Facebook use was found to be the strongest predictor of teachers' friending willingness. The implications of these findings and suggestions for future research are discussed. Highlights: Teachers' friending/unfriending willingness on Facebook are investigated. Teachers show willingness to friend students and colleagues. Intimacy and ethical concerns are influential in friending students. Privacy and FB use predict the friending of students with weak ties. FB use and privacy protection, but not intimacy, contribute to friending administrative colleagues.